Use Of The Marine Airbag Ship System In The Slipway Area Of The Shipyard - Mahendro, Iwan; Affariz, Nanda (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
PT. Citra Bahari Shipyard is a shipping company that uses Airbag Ship. Identification of hazards in the ship launching process using Job Safety Analysis(JSA) Guide Notes on the American Shipping Bureau (ABS) 2013, The procedures and processes that occur during the analysis and the equipment used are also what obstacles occur as well as solutions to these obstacles so that the launching process at PT. Citra Bahari Shipyard can run optimally. The purpose of hazard control measures in the launching process is to find out the potential hazards that can later cause work accidents and to obtain safe conditions from a launching process. The method that the observer uses is the method of directly observing the state of affairs in the field. Then conduct interviews with several parties related to ship launching and library study methods, namely by reviewing notes and reports that have to do with the launching of the ship with relevant sources. Then data processing is carried out to obtain control of the potential dangers and consequences that have been known so that it is hoped that potential hazards that cause injuries and material losses can be minimized. The result of this observation is that the control that has been carried out does not eliminate the danger completely, but minimizes the consequences of the potential dangers that exist from the ship launching process.